Effects of Soret and Dufour on Unsteady Magneto-Convective Transport through a Vertical Perforated Sheet with Chemical Reaction - Md. Mosharrof Hossain; Md. Hasanuzzaman; A. Rahim Laskar; Ashish Barmon (Advances in Mathematical Physics)
An investigation of the effects of Soret and Dufour on an unsteady MHD convective transmission over a vertical porous sheet with chemical reaction was introduced throughout this study. The model that formed nonlinear governing equations is transformed by applying the similarity analysis with the help of the finite difference method. The numerical resolutions of the fluid characteristics like velocity, concentration, and temperature are explained graphically. This research also presented the mass transmission rate, heat transmission rate, and the local skin friction coefficient, which are explained in tabular form. The results give the fluid motion and temperature improvement for growing values of the Dofour effect. Also, the fluid velocity and concentration improve for elevated amounts of the Soret effect. The local skin friction improves by around 66% whereas the mass transmission rate lessens by around 247% with the growing Soret number (0.5–2.0).